2007
DOI: 10.1097/sle.0b013e31806e61f4
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Minimally Invasive Percutaneous Nephrolithotomy on Renal Pelvic Pressure In Vivo

Abstract: Renal pelvic pressure generally remains lower than the level required for a backflow (30 mm Hg), during MPCNL via 14 to 18-Fr percutaneous tract. Any factor, which causes bad drainage, will result in a temporarily elevated renal pelvic pressure greater than 30 mm Hg; and multiple temporary high-pressure episodes can have a cumulative effect, which means that there will be enough backflow to cause a bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…Due to the pressure limit of renal parenchymal reflux is 30 mmHg [6], when the MPCNL is performed under high pressure perfusion it is easy to cause the intrapelvic pressure over 30 mmHg, and the operation manipulation, the integrity of the pelvic wall epithelium could be injured and thereafter leads to direct exposure of venous and lymphatic system followed by renal parenchyma reflux [7]; When the stones and infection occur at the same time, tissue edema and congestion are more likely to cause pelvic fluid absorption. A large amount of short-term liquid absorption can cause the perfusion fluid syndrome, and when the bacteria and its toxin reflux into the blood, complications like bacteremia, sepsis, or postoperative fever occur [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the pressure limit of renal parenchymal reflux is 30 mmHg [6], when the MPCNL is performed under high pressure perfusion it is easy to cause the intrapelvic pressure over 30 mmHg, and the operation manipulation, the integrity of the pelvic wall epithelium could be injured and thereafter leads to direct exposure of venous and lymphatic system followed by renal parenchyma reflux [7]; When the stones and infection occur at the same time, tissue edema and congestion are more likely to cause pelvic fluid absorption. A large amount of short-term liquid absorption can cause the perfusion fluid syndrome, and when the bacteria and its toxin reflux into the blood, complications like bacteremia, sepsis, or postoperative fever occur [8].…”
Section: Discussionmentioning
confidence: 99%
“…MPCNL surgery complication is related to the amount of liquid absorption. It is a positive correlation between the integrity of the epithelial cells, renal pelvic pressure, and the operation time [6, 9]. Performing MPCNL through irrigation can cause stones shift.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, in the past, the smaller working tract warned about the elevation of intrarenal pressure, which would induce the risks of bacteremia and sepsis. We once inspected that during mini-PCNL within the 14, 16, and 18 Fr percutaneous tracts, the average renal pelvic pressures were 24.85, 16.23, and 11.68 mmHg, respectively, all lower than the level required for a backflow (30 mmHg) [16]. The fluid in the pelvicalyceal system can be discharged easily.…”
Section: Discussionmentioning
confidence: 99%
“…Guohua et al. [35] investigated whether such a device contributed to high intrarenal pressures, promoting pyelovenous backflow. They found that the device created intrarenal pressures that were generally lower than the level required for backflow.…”
Section: Nephroscopesmentioning
confidence: 99%